A comparisoin of the R25 modification of Rappaport s enrichment medium with strontium chloride B for salmonella isolation from sewage polluted natural water. - Harvey, R. W. (Cambridge University Press, 1982)
The relation of salmonella isolation efficiency and the size of inoculum introduced from a buffered peptone water culture of sewage polluted water into strontium chloride B medium was investigated. Two separate studies were made, one using enrichment at 37 degrees C, the other at 43 degrees C. From these trials, two inocula suitable for efficient salmonella isolation were determined. Using this information, strontium chloride B medium was compared with modified Rappaport's broth (R25). The inoculum used with R25 was 0.005 ml, determined in an earlier study. Two incubation temperatures were employed with strontium chloride enrichment (37 and 43 degrees C). Rappaport's medium was incubated at 37 degrees C only. Elevated temperature enrichment at 43 degrees C improved the performance of strontium chloride B, but Rappaport's broth still gave significantly better results. This supports earlier studies on simplification of salmonella isolation and standardization of routine technique on a single enrichment medium: Rappaport broth (R25) incubated at 37 degrees C.